Pengaruh Promosi, Inovasi Produk, dan Digital Marketing terhadap Keputusan Pembelian Produk Batik Lochatara Wates Kabupaten Kediri - Arwenda Adyratna Putri D; Aprilia Dian Evasari; Endah Kurniawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The development of the batik industry today requires business actors to be able to implement effective marketing strategies in order to increase competitiveness and encourage consumer purchasing decisions. This study aims to analyze the effect of promotion, product innovation, and digital marketing on purchasing decisions for Batik Lochatara products in Wates, Kediri Regency. This research uses a quantitative method with a survey approach through distributing questionnaires to Batik Lochatara consumers in Wates, Kediri Regency. The analysis techniques used in this study include multiple linear regression, partial test (t test), simultaneous test (F test), and the coefficient of determination to determine the contribution of each independent variable to the dependent variable. The results of this study indicate that partially promotion, product innovation, and digital marketing have a positive and significant effect on purchasing decisions. While simultaneously, the three variables are also proven to have a significant influence on purchasing decisions with an adjusted R-square value of 0.743 or 74.3%. This means that purchasing decisions at Batik Lochatara can be explained by promotion, product innovation, and digital marketing by 74.3%, while 25.7% is influenced by other factors not studied. This finding confirms that the right promotional strategy, continuous product innovation, and digital marketing optimization are important factors in increasing consumer interest and purchasing decisions for local batik products in modern markets.